Jumpstart CMM/CMMI software process improvements : Using IEEE software engineering standards - Land, Susan K.; IEEE Xplore (Online Service); John Wiley & Sons ([United States] : $bWiley, 2006)
A brilliant instruction set for achieving CMM(a) and CMMI(a) Level 2 requirementsMany organizations, in their push to complete a successful Level 2 CMM or CMMI appraisal, make sizable investments to develop and document their software processes. This book helps these organizations save both time and money while skillfully moving from the chaos of a free-form software development process to one that is controlled, documented, and repeatable. Specifically, the author demonstrates how the application of select IEEE Software Engineering Standards ensures the production of higher quality, reproducible software products.Although the CMM and CMMI set forth standards in six Key Process Areas (KPAs) that must be satisfied to achieve Level 2 accreditation, they do not provide guidance on how to reach these standards. Readers will discover why that role should fall to the IEEE Software Engineering Standards, which, when applied effectively, can be used to develop best practices and fulfill the requirements associated with effective software project management. This book provides the link between Level 2 requirements and the supporting items available in the IEEE Software Engineering Standards. Using the detailed matrices that the author has designed to map Level 2 requirements to IEEE Software Engineering Standards, readers can better understand and meet the criteria set forth in all six KPAs.Everything needed to meet Level 2 requirements is provided:. Introduction and overview. Summary of SW-CMM. Summary of CMMI-SW (Staged). Differences between CMM and CMMI-SW (Staged). IEEE Software Engineering StandardsTechnical terminology for each phase of a CMM and a CMMI-SW model is explained in simple language making them easy to understand. For organizations that do not wish to pursue Level 2 accreditation, the book is still an essential resource that provides practical guidance for developing sound software engineering practices. This book is recommended for all software engineers, project managers, and auditors.
Preface. -- Acknowledgments. -- Tables and Figures. -- 1. Introduction and Overview. -- 2. Summary of SW-CMM(a). -- 3. Summary of CMMI-SW(a). -- 4. Differences Between CMM(a) and CMMI-SW(a). -- 5. IEEE Software Engineering Standards. -- 6. Using IEEE Standards to Achieve Software Process Improvement. -- Appendix A: IEEE Standards Abstracts. -- Appendix B: Level 2 Mappings of CMMI-E/SW/IPPD(a) V.1.1 to SW-CMM(a) V.1.1. -- Tables and Figures. -- References. -- Index.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Software engineering; Capability maturity model (Computer software); Electronic books